The Implementation of Classical Guidance using the 'Find Me' Game to Enhance High School Students' Self-defense Skills Against Bullying through Problem-Based Learning - Agustin, Prisca Aulia; Setyaputri, Nora Yuniar (IKIP Siliwangi, 2025)
This study aims to examine the effectiveness of implementing Problem-Based Learning (PBL) through the